Shexiang Baoxin Pill Corrects Metabolic Disorders in a Rat Model of Metabolic Syndrome by Targeting Mitochondria - Wei, Dan; Zheng, Ningning; Zheng, Lanyan; Wang, Leting; Song, Liang; Sun, Luning (Frontiers in Pharmacology, 2018)
Background: Metabolic syndrome (MS) is a global epidemic that has great socioeconomic and public health implications. This study reports observed effects of the Shexiang Baoxin Pill (SBP) in a rat model of MS and explores its underlying mechanisms of action. Methods: A diet-induced rat model of MS was established according to accepted methods, and the rats were randomly divided into two groups: a control group (0.9% NaCl, 100 mg/kg•d) and a SBP-treated group (SBP, 100 mg/kg•d). Systolic blood pressures, fasting blood glucose (FBS) levels, triglyceride (TG) levels, high-density lipoprotein cholesterol (HDL-C) levels, body weights, and abdominal perimeters were dynamically monitored and analyzed. Serum leptin, adiponectin, TNF-α, IL-6, and IL-10 levels were measured by ELISA. Leptin, adiponectin, TNF-α, IL-6, and IL-10 expression in adipose tissue, as well as AMP-activated protein kinase (AMPK) and peroxisome proliferator-activated receptor gamma coactivator 1-α (PGC-1α) expression in heart, liver, skeletal muscle, and adipose tissue was measured by western blot. Expression of the mitochondrial protein UCP2, Cytochrome b and ATPase was observed by immunofluorescent staining. Results: SBP significantly decreased serum TG, TC, LDL-C levels and increased HDL-C levels. SBP also optimized the leptin/adiponectin ratio by decreasing leptin expression and increasing adiponectin expression in adipose tissue. SBP antagonized inflammatory reactions by promoting IL-10 expression in adipose tissue while inhibiting TNF-α and IL-6 expression. SBP improved lipid metabolism by up-regulating the expression of AMPK and PGC-1α. Furthermore, SBP decreased the severity of MS and its complications by adjusting the expression of several mitochondrial proteins, including UCP2, Cytochrome b and ATPase. Conclusion: SBP exhibits prominent therapeutic effects in the setting of MS. Possible mechanisms of action may be related to its anti-inflammatory and anti-oxidative characteristics, as well as its effects on improving lipid metabolism and protecting mitochondrial function.